2016
DOI: 10.11144/javeriana.upsy15-1.ebpc
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Burden in Parents of Children With Trisomy 21. Descriptive Study in a Colombian Population

Abstract: a b S t r a c tThe role of a parent with a disabled child can be highly demanding. There are few publications concerning parental emotional exhaustion in Latin America. The present prevalent case-controlled study evaluated the frequency of emotional exhaustion in 103 parental couples of parents of children with Down Syndrome (DS); likewise the study explores the rate of emotionally exhausted and depressed mothers in comparison with the fathers. This outcome was measured using a modified and validated version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
15
1
7
Order By: Relevance
“…When we examined three different sub-dimensions in the Maslach Burnout Inventory, there was no significant difference between the parents for each of the three sub-dimensions in this study. This finding contradicts Jaramillo et al (2016) finding that being a mother increases the likelihood of emotional exhaustion. The authors reported that this distinction might be due to the fact that the mothers did not have a half-or full-time job-occupation.…”
Section: Discussioncontrasting
confidence: 94%
“…When we examined three different sub-dimensions in the Maslach Burnout Inventory, there was no significant difference between the parents for each of the three sub-dimensions in this study. This finding contradicts Jaramillo et al (2016) finding that being a mother increases the likelihood of emotional exhaustion. The authors reported that this distinction might be due to the fact that the mothers did not have a half-or full-time job-occupation.…”
Section: Discussioncontrasting
confidence: 94%
“…This adds confusion to an already disputed literature about the impact of gender on PCg burnout. Where some studies showed increases of burnout symptoms among mothers ( Jaramillo et al, 2016 ), others did not consistently find such a gender difference (e.g., Lindahl Norberg, 2007 ). Yet, there was no evidence of males experiencing more burnout symptoms than women in a caregiving context.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Maslach Burnout Inventory (MBI; Maslach and Jackson, 1981), the leading measure of burnout, was firstly used by Pelsma (1989). Subsequently, several different versions of job-burnout scales were applied to assess parental burnout, such as the MBI-Human Services Survey (Demirhan et al, 2011;Jaramillo et al, 2016;Vinayak and Rohin Kaur, 2017) and the Shirom-Melma Burnout Questionnaire (Norberg, 2007;Lindström et al, 2011;Norberg et al, 2014;Beheshtipour et al, 2016).…”
Section: Introductionmentioning
confidence: 99%